Rising mobility in Slavic i-stems - Kapović, Mate (Array, 2009)
In this article1 dealing with Slavic accentuation, the author points to the secondary spread of accentual paradigm c instead of the original accentual paradigm a in Slavic i-stems. It is claimed that the phenomenon of the rising mobility in i-stems begun already in Proto-Slavic and that is has continued to be active during the histories of all Slavic languages and dialects up to this day. Various examples are discussed, most notably the word *zvěrь „beast“ for which it is claimed that it was originally a. p. a and not a. p. c as usually reconstructed.